Legal Liability of Minors as Perpetrators of Online Buying and Selling Fraud in Indonesia - Tantimin Tantimin (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The development of internet technology is directly proportional to the growth of online trade. Easy access to online buying and selling transactions is faced with the risk of fraud, including the fraud committed by minors. This paper discusses the criminal liability of minors who commit criminal acts of fraud in online buying and selling transactions. The research method used was a normative legal research method. The results of this study indicate that online buying and selling transactions carried out by minors based on legal principles of engagement are legal. Fraud of online buying and selling transactions carried out by minors can be subject to criminal penalties by taking into account the rights of children under the Child Protection Act. Although children are not free from legal bondage, keeping children away from the formal justice process can avoid stigmatization of children in conflict with the law.